Motivation can improve medication adherence in hypertension patients - Yoga Tri Wijayanti; Zusana A Sasarari; Sumiyati Sumiyati; Prasetyowati Prasetyowati; Rusli Rusli (Jurnal Edukasi Ilmiah Kesehatan, 2024)
Introduction: Motivation is essential in improving medication adherence in hypertensive patients. Non-adherence to medication is often a significant obstacle in the management of high blood pressure, leading to an increased risk of serious complications such as heart disease and stroke. This study analyzes the relationship between patients' motivation levels and adherence to hypertension treatment regimens. Methods: The research design used is descriptive-analytical with a cross-sectional approach to hypertensive patients in a health clinic. Data were collected through questionnaires that measured motivation and adherence to medication. Results: The results of the analysis showed that patients with high motivation had better compliance levels than those with low motivation (p < 0.05). Contributing motivational factors include family support, understanding of the benefits of treatment, and confidence in managing the hypertension condition. Conclusions: Strong motivation plays a significant role in improving medication adherence in hypertensive patients, so health workers need to strengthen the motivational aspect of patient education and counseling programs. This is expected to help reduce the risk of complications and improve the quality of life of hypertensive patients.